Transforming Data into Knowledge: How to Improve the Efficiency of Clinical Care? - Séroussi, B; Soualmia, L. F; Holmes, J. H (Yearbook of Medical Informatics, 2017)
Objectives: To provide an introduction to the 2017 IMIA Yearbook of Medical Informatics by the editors.Methods: We present a brief overview of the 2017 special topic “Learning from experience: Secondary use of patient data”. We review our choice of special topic section editors, present the new section “Health Information Management”, and discuss transitions in the editorial team.Results: In this edition of the Yearbook, we focused on one of the most important issues for the medical informatics community: The secondary use of clinical data. With the ubiquitous adoption of electronic health records (EHRs) and the increasing availability of genomic and environmental data, as well as the accessibility of unstructured data in social media, issues related to data integration, storage, and management, as well as the need for novel analytic approaches are clear challenges. The paradigm of Learning Health Systems (LHSs) is presented in the keynote paper and survey papers review the significant developments in allied fields such as clinical research, clinical systems, translational informatics, and public health over the past two years. IMIA Working Groups also contributed to this topic.Conclusion: The 2017 issue of the IMIA yearbook focuses on the secondary use of patient data and presents the difficulties that still need to be solved before witnessing the actual development of LHSs.
Keywords: Informatics, Medical; Health Information Technology; IMIA Yearbook of Medical Informatics; Learning from experience; Secondary use of patient data